Family medicine residency training in Ghana after 20 years: resident attitudes about their education. Issue 4 (22nd October 2020) - Toma, Ghazwan; Essuman, Akye; Fetters, Michael D
Abstract : Objective: In addition to assessing educational needs of family medicine trainees in Ghana, we sought to assess whether those entering the training programme aimed to pursue an academic career. Design: A case study using an anonymous cross-sectional survey through collaboration between faculty members from the family medicine departments of Ghana and the University of Michigan. Setting: The family medicine postgraduate trainees and the most recent graduates in the three training sites, Accra, Kumasi and Mampong, as well as modular residents in Ghana served as the targeted participants during data collection between October and November of 2018. Participants: Second and third year family medicine residents, fellows (known as senior residents in Ghana) and recent graduates were invited to participate in this study. Thirty-five of 77 eligible subjects provided responses (46% response rate), but five records were eliminated due to incomplete data to yield a survey completion rate of 39% (30/77). Result: Participants were mostly men (n=19), and the average age of respondents was 37 years old. The participants indicated the residency programmes needed more faculty 97% (n=29), supervision during outpatient care 87% (n=26) and lectures 83% (n=25). The main reason provided by respondents for entering residency programme in family medicine, which is currently not required for practising primary care in Ghana, was to obtain more education 93% (n=28). Participants who had completed the residency programme were much more likely to be interested in becoming faculty compared with those still in residency (p <0.001). Conclusion: The research confirms the need for more faculty and the importance of investing in faculty development resources for ensuring a robust programme. These findings provide constructive feedback that could improve residency curricula of the local and regional family medicine training programmes and supports investing in trainees and new graduates as future faculty candidates.